Interspecific chromosomal-cytoplasmic staminal sterility and fertility in Nicotiana - Schweppenhauser, M. A.(Michael Andrew) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Agric.) -- University of Stellenbosch, 1965.